Svensk fraseologi för islänningar – om den isländsk-svenska ordboken i ISLEX och en onomasiologisk svensk resurs: Frasbanken - Hannesdóttir, Anna Helga; Tingsell, Sofia (LexicoNordica, 2011)
The ISLEX projects aim at developing an on-line dictionary site with Icelandic as the source language and the three Scandinavian languages as the target languages. This article presents the ISLEX projects, focusing on the phraseological aspects of the bilingual Icelandic- Swedish dictionary. It also describes the work on Frasbank en.se, an onomasiological electronic resource for presenting phrasemes in Swedish. Frasbanken.se is being developed to give additional phraseological information to users of the Icelandic-Swedish version of ISLEX, and is also meant to be used as a self-contained phraseological component for L2 and L1 speakers of Swedish. In developing Frasbanken.se, our main concern has been to meet the lexicographical and pedagogical needs of the L2 speaker with respect to phraseology. L2 speakers are known to acquire phraseological information at a late stage in their linguistic progress. Lack of phraseological competence can lead to complications for the learner; he or she needs to rely heavily on grammatical rules, failing to use prefabricated chunks, and the L2 speaker appears less idiomatic in his or her language production. Frasbanken.se is thus a well-directed resource for competent L1 speakers of Icelandic with Swedish as their L2.